Generation of active expiration by serotoninergic mechanisms of the ventral medulla of rats - Lemes, Eduardo V. [UNESP]; Colombari, Eduardo [UNESP]; Zoccal, Daniel B. [UNESP] (American Physiological Society, 2016)
Abdominal expiratory activity is absent at rest and is evoked during metabolic challenges, such as hypercapnia and hypoxia, or after the exposure to intermittent hypoxia (IH). The mechanisms engaged during this process are not completely understood. In this study, we hypothesized that serotonin (5-HT), acting in the retrotrapezoid nucleus/parafacial respiratory group (RTN/pFRG), is able to generate active expiration. In anesthetized (urethane, IP), tracheostomized, spontaneously-breathing adult male Holtzman rats we microinjected a serotoninergic agonist and antagonist bilaterally in the RTN/pFRG and recorded diaphragm and abdominal muscle activities. We found that episodic (3 times, 5 min apart), but not single microinjections of 5-HT (1 mM) in the RTN/ pFRG elicited an enduring (>30 min) increase in abdominal activity. This response was amplified in vagotomized rats and blocked by previous 5-HT receptor antagonism with ketanserin (10 μM). Episodic 5-HT microinjections in the RTN/pFRG also potentiated the inspiratory and expiratory reflex responses to hypercapnia. The antagonism of 5-HT receptors in the RTN/pFRG also prevented the long-Term facilitation (>30 min) of abdominal activity in response to acute IH exposure (10 × 6-7% O for 45 s every 5 min). Our findings indicate the activation of serotoninergic mechanisms in the RTN/ pFRG is sufficient to increase abdominal expiratory activity at resting conditions and required for the emergence of active expiration after IH in anesthetized animals.
Keywords: 5-Hydroxytryptamine; Active Expiration; Intermittent Hypoxia; Retrotrapezoid Nucleus/Parafacial Respiratory Group